Peran Filsafat Sejarah Dalam Menghasilkan Historiografi Bernilai Tinggi: Suatu Telaah - Prayogi, Arditya (Historis : Jurnal Kajian, Penelitian dan Pengembangan Pendidikan Sejarah, 2025)
Historical works or historiography are basically the result of historians' interpretations of trying to connect the present with the past. The interpretation results are then read and interpreted by the readers, sometimes beyond the interests of history itself. Reading historical works of course requires certain glasses. One of the glasses offered in this paper is the framework of the philosophy of history. On this basis, the writing of historical works will be closely related to the philosophy of history. This article aims to explain that the philosophy of history has a major role in producing high-value historiography. The research method used in writing this article uses a qualitative descriptive method based on literature study. The results showed that the philosophy of history, especially with its two scopes (speculative and critical), ultimately polarized historiography into historiography-philosophy and historiography-critical. These two forms of historiography have an important value in developing a tradition of multi-dimensional approaches to produce more valuable historical works.